Heterogeneous effects of government energy assistance programs: Covid-19 lockdowns in the Republic of Georgia - Anna Alberini; Levan Bezhanishvili; Milan Ščasný (Charles University in Prague, Institute of Economic Studies (IES), 2023)
During the Covid-19 pandemic, the governments of many countries adopted measures to support the population during the lockdowns and periods of reduced economic activity. In the Republic of Georgia, in April 2020 the government announced that it would pay the electricity bills of residential customers in April and May 2020, effectively making electricity free, as long as usage would not exceed 200 kWh/month. In August 2020, the government announced that the policy would be in force again in November and December 2020, and January and February 2021. We examine meter readings from the entire country outside of the Tbilisi city limits, finding that the average household increased usage by some 5% above and beyond their normal. This figure however masks considerable heterogeneity in the effects of the policy across urban, rural, and "high mountain" status areas. We examine the possibility that awareness of the policy might decrease with the distance from the capital Tbilisi, but find little evidence of "distance decay" effect. We find that, as suggested by economic theory, in the months when the policy is in place low-volume consumers increase their electricity usage and high-volume consumers decrease it in an effort to make the 200 kWh mark. Assuming that the increase in electricity demand was met with imports and domestic generation by gas-fired power plants, our models predict that in our sample CO2 emissions increased by 2,028 tons during the "free electricity months," despite an actual reduction among the residents of large cities.
Keywords: D12; Q41; Q48; 330; residential electricity consumption; increasing block rate (IBR) tariffs; salience; free electricity